THE INTEGRATION OF ISLAMIC COMMERCIAL AND SOCIAL ECONOMY THROUGH PRODUCTIVE WAQF TO PROMOTE PESANTREN WELFARE - Ratih Winarsih; Atika Rukminastiti Masrifah; Khoirul Umam (Journal of Islamic Monetary Economics and Finance, 2019)
A pesantren (Islamic boarding school) as an Islamic educational institution based on self-financing system has implemented waqf as a pillar of its development and become a potential waqf asset development. The productive waqf is considered as a key instrument for providing funds to actualizing its educational program. Since both productive waqf and pesantren emphasize sustainability, and since productive waqf can assist to support the process of education in pesantren, the study aims to investigate an integrated Islamic social and commercial economy model applicable in pesantren. This will ensure utilization of the combined resources of productive waqf and pesantren in promoting pesantren welfare. The study focuses on 263 operational chief, assatidz or teacher, musyrif, musyrifah or santri companion and santri or students in Pesantren in Java and Sumatra using. Structural Equation Modeling (SEM) adopted to examine the relationship among the five constructs i.e., productive waqf, business unit, project financing, human resource and pesantren welfare. While the reliability and validity are established, the structural relationship between the constructs reveals that the integrated model has a strong relationship with the pesantren welfare in many ways. In relation with business unit and profitable commercial activities, human resources have its significant role to assist pesantren tries its level best to realize developed productive waqf. Specifically, the result shows all five constructs have significant impact in promoting pesantren welfare, which suggests that the model as well as the instrument should be further implemented in pesantren.